A new idea for ambulance location problem in an environment under uncertainty in both path and average speed: Absolutely robust planning. (November 2019) - Akıncılar, Aykan; Akıncılar, Ece
Highlights: Ambulance location problem under 2-dimensional uncertainty is focused on. Average speed of ambulances and the path that they use are assumed uncertain. Plans which are entirely immunized against 2-dimensional uncertainty are produced. Several thresholds for arriving at the event scene and several average speeds are experienced. Cost-efficiency of those plans are tested via real dataset. Abstract: When human life is the point in question, plans of healthcare transportation in an urban area must be immunized against uncertainty as much as possible due to its vital impact on many aspects. At this point, absolutely robust and also cost-efficient plans in healthcare transportation in an urban area are surely desired. Unfortunately, for ambulance location problem (ALP) in an environment under uncertain distance of path that emergency vehicle uses and uncertain average speed of the emergency vehicle, an absolutely robust plan has not yet been achieved. Therefore, in this study, a new model providing absolutely robust and also cost-efficient plans for ALP in an environment under two-dimensional uncertainty is clearly achieved. In addition, according to the best knowledge of the authors, this work is one of the precessor implementations that demonstrate robust counterpart (RC) approach can provide incredibly beneficial and useful results for the ALP. The proposed model is developed via utilizing RC approach, which is a very convenient tool for the main goal of this study. For the sake of demonstrating how the proposed model works in real life and what the results are, a case study is employed, which is tested in a simulation process under several scenarios in order to increase reliability. Results being obtained by the case study demonstrate that the proposed model works well and absolutely robust solutions are able to be obtained in return significantly sufferable costs for all of the scenarios. It is hoped that a crucial gap in the literature is -at least partially- filled by the proposed model.